Environmental Vulnerability and the Application of Green Criminology in Bangladesh: Examining Legal Gaps and Social Justice - MIA, Md. Tuhin; Hamide, Md. Shamim; Huda, Md. Nazmul (Faculty of Law, Universitas Gadjah Mada, 2025)
Abstract Green criminology provides a critical framework for understanding environmental harm as both a legal and social injustice, especially in regions disproportionately affected by climate change. In the context of Bangladesh—where ecological degradation intersects with poverty, displacement, and state inaction—this study examines how existing environmental laws and regulatory mechanisms fall short of protecting vulnerable communities and ecosystems. Using a qualitative methodology grounded in criminological and legal analysis, the paper interrogates the structural weaknesses in Bangladesh’s environmental governance, highlighting enforcement gaps, policy ambiguities, and the marginalization of affected populations in decision-making processes. Rooted in the principles of green criminology, this model envisions a justice system that goes beyond punitive responses to embrace sustainability, inclusiveness, and ecological accountability. The study ultimately demonstrates how criminological theory can inform a more holistic and equitable approach to environmental law in Bangladesh. Abstrak Green criminology menyediakan kerangka kritis untuk memahami kerusakan lingkungan sebagai ketidakadilan yang bersifat hukum sekaligus sosial, khususnya di wilayah-wilayah yang terdampak perubahan iklim secara tidak proporsional. Dalam konteks Bangladesh—di mana degradasi ekologis beririsan dengan kemiskinan, perpindahan penduduk, dan kelalaian negara—kajian ini menelaah bagaimana hukum lingkungan dan mekanisme regulasi yang ada belum mampu melindungi komunitas rentan dan ekosistem secara efektif. Dengan menggunakan metodologi kualitatif yang berlandaskan analisis kriminologis dan hukum, artikel ini mengkaji kelemahan struktural dalam tata kelola lingkungan di Bangladesh, dengan menyoroti kesenjangan penegakan hukum, ambiguitas kebijakan, serta marginalisasi kelompok terdampak dalam proses pengambilan keputusan. Berakar pada prinsip-prinsip green criminology, model ini membayangkan sistem keadilan yang melampaui respons yang semata-mata bersifat represif dengan mengedepankan keberlanjutan, inklusivitas, dan akuntabilitas ekologis. Studi ini pada akhirnya menunjukkan bagaimana teori kriminologi dapat berkontribusi pada pendekatan hukum lingkungan yang lebih holistik dan berkeadilan di Bangladesh.